CT Colonography in Colorectal Cancer Screening: Identifying Risk Factors for the Detection of Advanced Neoplasia - Hassan, Cesare (2013)
BACKGROUND: Our aim was to determine if age, sex, positive family history (FH+) for colorectal cancer, and body mass index (BMI) are important predictors of advanced neoplasia in the setting of screening CT colonography (CTC). METHODS: Consecutive patients referred for first-time screening CTC from 2004 to 2011 at a single medical center were enrolled. Results at pathology were recorded for all patients undergoing polypectomy. Logistic regression was used to identify significant predictor variables for advanced neoplasia (any adenoma ≥10mm or with villous component, high-grade dysplasia, or adenocarcinoma). Odds ratio (OR) was used to express the association between study variables (age, sex, BMI and FH+) and advanced neoplasia. RESULTS: 7,620 patients underwent CTC screening. Of these, 276 (3.6%; 95% CI: 3.2–4.1%) were ultimately diagnosed with advanced neoplasia. At multivariate analysis, age (mean OR per 10-year increase: 1.8; 95% CI: 1.6–2) and male sex (OR: 1.7; 95% CI: 1.3–2.2) were independent predictors of advanced neoplasia, whereas BMI and FH+ were not. Number needed to screen (NNS) to detect one case of advanced neoplasia varied from 51 in women ≤55 years to 10 in men >65 years. The number of post-CTC colonoscopies needed to detect one case of advanced neoplasia varied from two to four. CONCLUSIONS: Age and sex were important independent predictors of advanced neoplasia risk in subjects undergoing screening CTC, whereas BMI and positive family history were not. These results have implications for appropriate patient selection.